2012
DOI: 10.1021/la3004118
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Shape Selectivity in the Liquid-Phase Adsorption of Xylene Isomers in Zirconium Terephthalate MOF UiO-66

Abstract: Microemulsions are nanoheterogeneous, thermodynamically stable, spontaneously forming mixtures of oil and water by means of surfactants, with or without cosurfactants. The pledge to use small volumes of amphiphile molecules compared to large amounts of bulk phase modifiers in a variety of chemical and industrial processes, from enhanced oil recovery to biotechnology, fosters continuous investigation and an improved understanding of these systems. In this work, we develop a molecular thermodynamic theory for dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(102 citation statements)
references
References 36 publications
5
97
0
Order By: Relevance
“…220 Two patents have been recently filed by this company concerning a MOF compound and its preparation method (WO2013160683A1, filed in 2013), 221 and another method of MOFs manufacture resulting in high surface area compounds (WO2014114948A1, filed in 2014). [222][223][224][225][226][227][228][229][230][231] It is important to emphasize that the thermal stability of MOFs is usually limited to temperatures below 400 ºC, which somehow reduces their potential with respect to applications at high temperatures. Both thermal and chemical stability and efficiency/cost ratio are crucial when studying MOFs for catalytic purposes.…”
Section: -Transportation and Oleochemical Industrymentioning
confidence: 99%
“…220 Two patents have been recently filed by this company concerning a MOF compound and its preparation method (WO2013160683A1, filed in 2013), 221 and another method of MOFs manufacture resulting in high surface area compounds (WO2014114948A1, filed in 2014). [222][223][224][225][226][227][228][229][230][231] It is important to emphasize that the thermal stability of MOFs is usually limited to temperatures below 400 ºC, which somehow reduces their potential with respect to applications at high temperatures. Both thermal and chemical stability and efficiency/cost ratio are crucial when studying MOFs for catalytic purposes.…”
Section: -Transportation and Oleochemical Industrymentioning
confidence: 99%
“…This observation is consistent with the work of Kim et al 26 who observed the addition of poly(vinyl alcohol) as binder in MOF composites resulted in over a 40% decrease in the observed surface area. Moreira et al 43 made a similar observation noting more than a 20% drop in surface area for graphite/UiO-66 composites. 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 …”
Section: Materials Characterizationmentioning
confidence: 70%
“…The first experimental study conducted for hexane and xylene isomers mixtures shows that the adsorption order of structural isomers in UiO 66 is opposite to the one observed in conventional adsorbents (Bárcia et al, 2011). This reverse shape selectivity was also observed for the xylene isomers adsorption in liquid phase, using n-heptane as eluent (Moreira et al, 2012).…”
Section: Introductionmentioning
confidence: 94%